Trinidad and Tobago : 2005 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that the macroeconomic performance and financial developments in Trinidad and Tobago are currently being driven by a highly favorable external environment. Surging oil prices have strengthened the external current account balance, financed an expansion of aggregate demand, and contributed to high levels of liquidity in the financial system. There are tentative signs that the economy is producing at, or near, capacity, and inflation pressures are emerging. Financial markets have generally been buoyant in reflection of the ample liquidity.